Pemikiran Teologi Maturidiyyah (Pendekatan Sejarah) - Ahmad Shofi Muhyiddin (UPT Pusat Studi Aswaja UNISNU Jepara, 2022)
AbstractThe birth of the major schools of classical theology cannot be separated from the political dynamics that occurred in the early days of the history of Muslims. At specific points, these dynamics then give rise to problems that are at the same time central issues in the realm of theology. Māturīdiyyah emerged as a response to Mu'tazilah thought but on the other hand, it is also closer to the Mu'tazilah school because it gives greater authority to reason. Therefore, this study aims to determine the theological thinking of Maturidiyah. This literature research uses a historical approach with the assumption that the behavior and theological thoughts of an individual and a religious community cannot be explained and understood apart from the ties of influence or the social, political, and cultural factors surrounding them. The results of this study indicate that the emergence of the Māturīdiyyah school was motivated by al-Māturīdī's dissatisfaction with the rationalist (Mu'tazilah) and traditionalist (Hanbaliyyah)methods of kalam, as well as concerns over the widespread understanding of the Qarāmiṭah Shi'ism which was heavily influenced by the Mazdakism and Manichaeism schools. The Māturīdiyyah school was heavily influenced by the thoughts of Ab anīfah and the heterogeneous conditions of its society so that its theological thinking was close to the Mu'tazilah. For Al-Māturīdī, there is only one knowledge, namely religious knowledge which is based on two sources, namely as-sam' (tradition) and al-'aql (reason). As for the theory of action, according to al-Māturīdī, the servant's actions (af'āl al-'ibād) if attributed to Allah then mean creation (khalqan wa jādan). However, if the servant's actions (af'āl al-'ibād) are attributed to humans, it means effort (fi'lan wa kasban).Keywords: Thought, Theology, Māturīdiyyah.AbstrakLahirnya mazhab-mazhab besar teologi klasik tidak terlepas dari dinamika politik yang terjadi padamasa-masa awal perjalanan sejarah umat Islam. Pada titik-titik tertentu dinamika ini kemudian melahirkan persoalan-persoalan yang sekaligus merupakan isu-isu sentral dalam ranah teologi. Māturīdiyyah muncul sebagai respon terhadap pemikiran Mu’tazilah namun di sisi lain juga lebih dekat pada mazhab Mu'tazilah karena lebih memberikan otoritas yang besar pada akal. Oleh karena itu, penelitian ini bertujuan untuk mengetahui pemikiran teologi Maturidiyah. Penelitian kepustakaan ini menggunakan pendekatan sejarah dengan asumsi tingkah laku dan alam pikiran teologis seorang individu dan masyarakat beragama tidak bisa diterangkan dan dimengerti lepas dari ikatan pengaruh atau faktor-faktor sosial, politik dan kebudayaan yang mengitarinya. Hasil penelitian ini menunjukkan bahwa lahirnya aliran Māturīdiyyah dilatarbelakangi oleh rasa tidak puas al-Māturīdī terhadap metode kalam kaum rasionalis (Mu'tazilah) dan kaum tradisionalis (Hanbaliyyah), serta kekhawatiran atas meluasnya paham Syi’ah Qarāmiṭah yang banyak dipengaruhi oleh aliran Mazdakism dan Manichaenism. Aliran Māturīdiyyah banyak dipengaruhi oleh pemikiran Abū Ḥanīfah serta kondisi masyarakatnya yang heterogen sehingga pemikiran teologisnya dekat dengan Mu'tazilah. Bagi Al-Māturīdī, hanya ada satu pengetahuanyaitu pengetahuan keagamaan yang didasarkan atas dua sumber yaitu as-sam' (tradisi) dan al-’aql (akal). Adapun tentang teori perbuatan, menurut al-Māturīdī, perbuatan hamba (af'āl al-'ibād) jika dinisbatkan kepada Allah maka bermakna peciptaan (khalqan waījādan). Namun jika perbuatan hamba (af'āl al-'ibād) dinisbatkan pada manusia maka bermakna usaha (fi’lan wa kasban).Kata kunci: Pemikiran, Teologi, Māturīdiyyah.